Sifat Kimia, Mikrobiologi dan Organoleptik Yogurt yang Menggunakan Persentase Lactobacillus casei dan Kadar Gula yang Berbeda - Yusdar Zakaria (Agricultural Faculty, 2008)
Chemical, microbiological and organoleptical of yogurt using the different of percentage lactobacillus casei and sugar levelABSTRACT. The objective of this study is to know quality of yogurt with variant of percentage Lactobacillus casei and sugar level. The parameter of this study were the crude protein applying the Kjeldhal method, the crude fat applying the Gerber method, the sum of amount of alive of micro-organism applying the plate count method and the organoleptic applying the square of. The result of this study showed that the different of sugar level is significant (P0.05) on crude protein and crude fat, however the different of percentage L casei not significant (P 0,05) on all parameter. The interaction is only found between two factors on crude fat. The highest of the rate amount of alive microorganism, crude protein and acetic acid are found in yogurt using 10% L. casei and 15% sugar level. From organoleptic test, its found that yogurt using 10% L. casei and 15% sugar level is the most prevered kind of yogurt.